Financial Sector Development in the Pacific Rim 2009
DOI: 10.7208/chicago/9780226386867.003.0013
|View full text |Cite
|
Sign up to set email alerts
|

Listing Policy and Development of the Tokyo Stock Exchange in the Prewar Period

Abstract: Recent studies have established that the Japanese stock market had a substantial size in the prewar period, and played an important role in financing economic development. The prewar stock market in Japan, however, did not achieve its size and status quickly. Indeed, the market capitalization stayed relatively small during the early years of the stock market development in Japan. This paper studies the prewar development of the Tokyo Stock Exchange, which eventually grew to be one of the two largest stock exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Moreover, between 1914 and 1929, as much as 14.9 per cent of Japanese corporate finance was raised through the issuance of corporate bonds on these exchanges and only 4.1 per cent through bank credit (Hamao et al. ; Dalglish and Moore ).…”
Section: How Big Was the Shanghai Bourse In Global Terms?mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, between 1914 and 1929, as much as 14.9 per cent of Japanese corporate finance was raised through the issuance of corporate bonds on these exchanges and only 4.1 per cent through bank credit (Hamao et al. ; Dalglish and Moore ).…”
Section: How Big Was the Shanghai Bourse In Global Terms?mentioning
confidence: 99%
“…By 1938, the ratio of stock to GDP had climbed as high as 181 per cent in Japan but edged only slightly upward to 56 per cent in the USA. Hamao et al (2009) found that despite gaps in size, population, and wealth between the two countries, the same number of firms were listed in Tokyo in 1936 as in New York. Tokyo was also a very sophisticated equity market, where the trade in futures was one of the most extensive in the world at the time.…”
Section: How Big Was the Shanghai Bourse In Global Terms?mentioning
confidence: 99%
See 1 more Smart Citation
“…The spot market appears to have comprised many small firms and have been very illiquid. Hamao et al (, p. 17) state that “it seems safe to conclude that the TSE did not have explicit listing criteria for the spot market.” Most positions taken on large firms occurred via the futures market. The Ministry of Agriculture and Commerce imposed the following requirements on the futures market in 1914: (i) the firm must be at least two years old; (ii) the total paid‐in nominal value must be at least one million yen (approximately $0.5 million); and (iii) if a firm already had shares traded on the futures market, subsequent issues needed to have a paid‐in nominal value of at least 500,000 yen…”
Section: History Of Futures Markets and Futures Pricingmentioning
confidence: 99%
“…For example, Asahi Shimbun and Yomiuri Shimbun, leading Japanese-language daily newspapers, have only slightly more futures listed (and somewhat different coverage) than The Japan Times and Mail. Kabukai 20nen covers more of the securities listed on the TSE, but far fewer than the number of listings reported by Hamao et al (2009). The TSE itself only began publishing official price lists in 1949.…”
Section: Datamentioning
confidence: 99%